Nominee Agreement Made For The Purposes Of Land Ownership By Foreign Citizens On The Basis Of ANotarial Deed - Luh Putu Sudini; I Wayan Kartika Jaya Utama (Warmadewa Press, 2018)
National land laws prohibit the ownership right of land by foreigners as reflected in the provisions of Article 9 UPPA, the Basic Agrarian Law, which confirm that only Indonesian citizens who can have ownership rights on the land. In addition, the provisions of Article 26 Paragraph (2) UUPA also prohibit the transfer of ownership of land from the citizen of Indonesian to foreign citizen, both directly and indirectly. Legal consequences of the deed of agreement of the land ownership rights of Indonesian citizen by foreign citizens made by a notary public is null and void because the objective conditions are not met, as postulated by Article 1320 of the Civil Code. Indeed ownership rights to land by foreign citizens, either directly or indirectly does not promise a legal protection to the party concerned.